Inhibition of the proliferation, migration, and invasion of human breast cancer cells by leucine aminopeptidase 3 inhibitors derived from natural marine products. Issue 1 (January 2020) - Yang, Hanlin; Dai, Gong; Wang, Sensen; Zhao, Yan; Wang, Xuejuan; Zhao, Xin; Zhang, Hongan; Wei, Liuya; Zhang, Lei; Guo, Shoudong; Song, Weiguo; Guo, Lu; et al.
Abstract : Leucine aminopeptidase 3 is involved in the progression and metastasis of several cancers. This study aimed to screen anti-tumor lead compounds targeting leucine aminopeptidase 3. The compounds' suppression effect on enzyme activity and anti-tumor activity were evaluated through a series of assays. Leucine aminopeptidase 3 overexpression K562 cells were used as an enzyme source to screen 43 natural marine compounds. Compounds 5 and 6 exhibited high suppression effect on leucine aminopeptidase 3 activity. Cell activity tests indicated that both compounds have an anti-proliferative effect on triple-negative breast cancer cells. Wound healing assay and transwell invasion assay showed that both compounds could inhibit the migration and invasion of breast cancer cells. Immunoblot analysis exhibited that both compounds could downregulate the expression of metastasis-related proteins fascin and matrix metalloproteinase-2/9. A molecular dynamic simulation process was applied to discover the key features of compounds 5 and 6 in binding to leucine aminopeptidase 3 active site. This study described the anti-tumor effects of two leucine aminopeptidase 3 small molecule inhibitors. Taken together, compounds 5 and 6 could be used as anti-tumor lead compounds targeting leucine aminopeptidase 3.